Evaluasi Keandalan Catatan Akuntansi Persediaan dalam Pelaksanaan Pengendalian Intern (Studi Kasus Pada CV Juberta di Kasui, Way Kanan) - Iskandar Ali Alam; Krukas Pari; Syamsu Rizal (Jurnal Akuntansi dan Keuangan, 2010)
The purpose of this study was to determine whether inventory records in the implementation of internal control has been reliably. Authors proposed hypothesis is: "inventory accounting records in the implementation of internal control has not been reliably. The methods used in the research is to conduct library research, especially on things that relate to research and field research by way of field research with the object studied. Analysis tool used is the qualitative analysis was to compare the theory internal control systems inventory with field reality. In the discussion of the data analysis, it can be concluded that based on the qualitative analysis that in carrying out its activities CV.Juberta leaders had planned organizational structure and division of tasks according to the activities undertaken, the transfer of goods to the companys procedures do not ensure good internal control, because it contains among the many weaknesses lain.selama pngiriman process and storage of goods in warehouses holding just rely on trust to a warehouse clerk. The company has not separated the functions of making the order and delivery of goods, storage, and delivery functions.